Análise numérica detalhada de escoamentos multifásicos bidimensionais - Villar, Millena Martins (2007)
The mathematical modeling of multiphase flows involves the interaction between deformable and moving geometries with the fluid in which they are dispersed (immersed). This kind of interaction is present in many practical applications. A common approach to handle these problems is the so called Front-Tracking/Front-Capturing Hybrid Methods. This methodology consists in separating the problem into two domains: an eulerian domain, which is kept fixed and is used to discretize the fluid equations of both phases, and a lagrangian domain, which is used to solve the equations of motion of the interface. Since there is no geometric dependence between these two domains, the method can easily handle moving and deformable interfaces that are dispersed in the flow. Following this line of research, the present work aims to capture accurately details of such flows by resolving adequately the relevant physical scales in time and in space. This can be achieved by applying locally refined meshes which adapt dynamically to cover special flow regions, e.g. the vicinity of the fluid-fluid interfaces. To obtain the required resolution in time, a semi-implicit second order discretization to solve the Navier-Stokes equations is used. The turbulence modeling is introduced in the present work through Large Eddy Simulation. The eficiency and robustness of the methodology applied are verified via convergence analysis, as well as with simulations of one-phase and two-phase flows for several Reynolds numbers. The results of two-phase flows, with one bubble and with multiple bubbles, are presented. The results obtained for a single bubble case are compared with Clift's shape diagram (Clift et al., 1978).